The Directive-Commissive Continuum - Lorena Pérez Hernández (Miscelánea: A Journal of English and American Studies, 2001)
In recent years, linguistics has increasingly focused its interest on the realm of texts, trying to find in them links of a similar nature to those working in sentences. An important contribution in this respect was that of Danes (1974), who used the term “Thematic progression” to refer to the “choice and ordering of utterance themes” in a given passage. However, in my opinion, thematic progression only indicates the connections between the different textual segments without clarifying their nature. This article wishes to provide thematic progression with the necessary means to identify the relations established in a text, and for that purpose I will use both its cohesive resources (Halliday and Hasan 1976) and its semantic relations (Alcaraz 1982). The network we obtain is shown graphically with the help of an extended notation system.